The Effectiveness of Rational Emotive Behavior Therapy (REBT) in Managing Anger among Dormitory Students: A QUALITATIVE CASE STUDY - JOHANA BETRIS TUMBOL; TAURISIA TRIFOSA; EUNIKE WIRAWAN; EVI YUSUF (Institut Agama Kristen Negeri Kupang, 2026)
This study examines the issue of anger among dormitory students influenced by irrational beliefs. The objective is to analyze the effectiveness of Rational Emotive Behavior Therapy (REBT) in managing such emotional responses. A descriptive qualitative approach was employed, utilizing primary and secondary data collected through counseling interviews, observations, and documentation. Data were analyzed through systematic processes of reduction, display, and conclusion drawing. The findings indicate that REBT successfully transforms irrational beliefs into rational thinking patterns, leading to reduced anger intensity, improved self-control, and better social interactions among students. Therefore, REBT proves to be an effective intervention approach for fostering adaptive emotional regulation in academic residential settings